2016
DOI: 10.18632/oncotarget.11764
|View full text |Cite
|
Sign up to set email alerts
|

High expression of microRNA-454 is associated with poor prognosis in triple-negative breast cancer

Abstract: MicroRNA-454 (miR-454) has been reported to play an oncogenic or tumor suppressor role in most cancers. However, the clinical relevance of miR-454 in breast cancer remains unclear. We examined the expression of miR-454 in a tissue microarray containing 534 breast cancer specimens from female patients at Fudan University Shanghai Cancer Center using in situ hybridization (ISH). Of these, 250 patients formed the training set and the other 284 were the validation set. The relationship between miR-454 and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…[17] No significant heterogeneity was observed across studies (OS, I 2  = 0.00%, P  = .925; DFS, I 2  = 0.00%, P  = .949). The fixed-effects model revealed that miR-454 expression was inversely associated with OS (combined adjusted HR: 6.74; 95% CI: 2.72–16.73) and DFS (combined adjusted HR: 3.72; 95% CI: 1.94–7.12) in TNBC patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[17] No significant heterogeneity was observed across studies (OS, I 2  = 0.00%, P  = .925; DFS, I 2  = 0.00%, P  = .949). The fixed-effects model revealed that miR-454 expression was inversely associated with OS (combined adjusted HR: 6.74; 95% CI: 2.72–16.73) and DFS (combined adjusted HR: 3.72; 95% CI: 1.94–7.12) in TNBC patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al (32) indicated that miR-141/200c was involved in TNBC migration and invasion via activating the focal adhesion kinase and phosphoinositide 3-kinase/AKT signaling pathways. miRNA-454 was revealed to be associated with poor prognosis in TNBC (17) and miRNA-200b could suppress TNBC metastasis by regulating protein kinase C α (19). Furthermore, miR-211-5p served a tumor suppressor role in TNBC progression by targeting SETBP1 (33) and miRNA-21 could promote TNBC cell proliferation and invasion by regulating phosphatase and tensin homolog (34).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have indicated that abnormal expression of miRs is associated with human breast cancer (11)(12)(13)(14)(15)(16). Furthermore, mounting evidence indicates that miRs serve key functions in the development of TNBC (17)(18)(19). However, the exact molecular mechanism of miRs in TNBC is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous miRNAs have been investigated as prognostic and diagnostic biomarkers and therapeutic targets. Cao et al revealed that miR-454 overexpression was correlated with unfavorable prognosis for patients with triple-negative breast cancer [24]. In the study of Wei et al, they reported that miR-1 was signi cantly downregulated in recurrent PCa tissues and it can function as an independent predictive factor for PCa [25].…”
Section: Discussionmentioning
confidence: 99%